2014
DOI: 10.1080/00028487.2014.892536
|View full text |Cite
|
Sign up to set email alerts
|

Potential Fitness Benefits of the Half‐Pounder Life History in Klamath River Steelhead

Abstract: Steelhead Oncorhynchus mykiss from several of the world's rivers display the half‐pounder life history, a variant characterized by an amphidromous (and, less often, anadromous) return to freshwater in the year of initial ocean entry. We evaluated factors related to expression of the half‐pounder life history in wild steelhead from the lower Klamath River basin, California. We also evaluated fitness consequences of the half‐pounder phenotype using a simple life history model that was parameterized with our empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…It is unclear whether some of these fish may forgo migration to the ocean and remain in freshwater essentially as a Rainbow Trout. In native steelhead populations from rivers of northern California, southern Oregon, and eastern Russia, there exists a unique life history variant referred to as the "half-pounder," a name descriptive of their relatively small size (Snyder 1925;Kesner and Barnhart 1972;Savvaitova et al 2005;Hodge et al 2014). Half-pounders return to freshwater after only 2-4 months in seawater, can be both male and female, and are predominantly immature (Kesner and Barnhart;Everest 1973;Hodge et al 2014).…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…It is unclear whether some of these fish may forgo migration to the ocean and remain in freshwater essentially as a Rainbow Trout. In native steelhead populations from rivers of northern California, southern Oregon, and eastern Russia, there exists a unique life history variant referred to as the "half-pounder," a name descriptive of their relatively small size (Snyder 1925;Kesner and Barnhart 1972;Savvaitova et al 2005;Hodge et al 2014). Half-pounders return to freshwater after only 2-4 months in seawater, can be both male and female, and are predominantly immature (Kesner and Barnhart;Everest 1973;Hodge et al 2014).…”
mentioning
confidence: 99%
“…In native steelhead populations from rivers of northern California, southern Oregon, and eastern Russia, there exists a unique life history variant referred to as the "half-pounder," a name descriptive of their relatively small size (Snyder 1925;Kesner and Barnhart 1972;Savvaitova et al 2005;Hodge et al 2014). Half-pounders return to freshwater after only 2-4 months in seawater, can be both male and female, and are predominantly immature (Kesner and Barnhart;Everest 1973;Hodge et al 2014). However, several investigators have reported that some half-pounders return from the ocean and precociously mature in freshwater at age 2 (Kesner and Barnhart 1972;Savvaitova et al 2005;Hodge et al 2014).…”
mentioning
confidence: 99%
See 3 more Smart Citations